Practical radio resource management in wireless systems - Kyriazakos, Sofoklis A., 1975- (Artech House universal personal communications series., 2004)
Despite frustrating customers and loss of revenue for telecommunications providers, cellular network congestion has remained a problem for which few solutions have been found. Covering GSM, GPRS, UMTS and beyond 3G systems, this practical book breaks new ground by providing you with proven techniques for decreasing blocking and dropped call rate due to network congestion. Using real measurements, this book clearly shows you that the maximum traffic that can be accommodated in a wireless network is not a constant value and varies significantly.